The Snake: A Slithery Patient, Difficult to Grasp - Leupen, Alex; Heijnen, Denise (Homœopathic Links, 2017)
Alex Leupen has worked in the Homeopathic Doctors Centre in Utrecht, the Netherlands, since 1990. Nine colleagues work in this centre, including Jan Scholten. Alex is an experienced teacher (the Netherlands, Belgium and Germany) on the underlying systems in the plant families, animal kingdom, sarcodes, nosodes, fungi and the periodic table of the elements pertaining to homeopathic practice. In this column, he shares clinical tips.This edition of his column is written together with veterinary surgeon Denise Heijnen.
Keywords: Snakes; Aethusa; Ignis alcoholicus; Sulfur; Psorinum